2021
DOI: 10.1088/2051-672x/ac3a53
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization for enhanced tribological properties of Al/MWCNT composites produced by powder metallurgy using artificial neural networks

Abstract: In order to eliminate the agglomeration problem of reinforcement in the nanocomposite, a two-step dispersion process was employed. Under ultra-sonication and ball milling, 1 wt% of multi-walled carbon nanotubes (MWCNTs) were properly dispersed in pure aluminum (Al) (used as the matrix phase). The composite powder mixture was then consolidated in an inert Ar gas atmosphere by hot pressing under certain fabrication parameters. The powder mixture was characterized by Raman Spectroscopy, and it was found that MWCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In the literature, it is possible to identify several production routes for MMNCs. Still, powder metallurgy is an efficient, simple, accessible, and widely used technique for manufacturing these nanocomposites [10][11][12]. The powder metallurgy process can be subdivided into four key steps, starting with the powder mixing and dispersion with the metal powder and reinforcement, followed by the pressing and the sintering of the samples [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it is possible to identify several production routes for MMNCs. Still, powder metallurgy is an efficient, simple, accessible, and widely used technique for manufacturing these nanocomposites [10][11][12]. The powder metallurgy process can be subdivided into four key steps, starting with the powder mixing and dispersion with the metal powder and reinforcement, followed by the pressing and the sintering of the samples [13].…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the wear properties of the MWCNTs/Al nanocomposites could be accurately assessed using the artificial neural network technique. 20 The development of functionalized multiwalled carbon nanotubes-aluminum (f-MWCNTs/Al) nanocomposite for industrial applications is still in its early stages. As a result, a better understanding of fabrication process parameters is required for industrial applications of this nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the wear properties of the MWCNTs/Al nanocomposites could be accurately assessed using the artificial neural network technique. 20…”
Section: Introductionmentioning
confidence: 99%